Onset of the Non-Medical Use of Prescription and Over-the-Counter Medications during Early Adolescence: Comparison with Alcohol, Tobacco, and Marijuana - Sarosh Khan; Kenneth W. Griffin; Gilbert J. Botvin (MDPI AG, 2023)
This study examined the prevalence and psychosocial predictors of the non-medical use of prescription and over-the-counter (OTC) medications and compared these to cigarette, marijuana, and alcohol use in a cohort of early adolescents (N = 1887) aged 11 to 13, a critical risk period for the initiation of substance use. Participants were students attending 22 middle schools in the northeastern United States. Participants completed surveys in the classroom, the first in the sixth grade and a second in the seventh grade, and the rate of overall substance use more than doubled from 5.5% to 11.9% over this period. Predictors of the onset of non-medical prescription and over-the-counter drug misuse overlapped substantially with those for marijuana and other substances. The perception of friends' substance use and the belief that substance use can help you deal with problems predicted the onset of marijuana use, OTC medication misuse, and prescription drug misuse. Decision-making skills were protective for the onset of all substance use outcomes. The findings of this study have important implications for prevention and suggest that a single comprehensive approach may be sufficient for preventing multiple forms of substance use onset during early adolescence.